Mushaf Kuna Tulisan Tangan dari Yaman Selatan - Ahmad Fathoni (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2007)
Al-Qur'an that revealed to the prophet Muhammad saw in not in one reading/recitation way, but in seven waysaccording to Hadis: Revealed wit sab'atu ahruf. Unfortunately, Indonesian Muslim peoples did not know about this.They only knew that Al-Qur'an fro the beginning until this time is based on ashim reading way that transmitted fromHasfh (d. 180 H)